Impact of a peer-to-peer escape room activity in the learning of Human Physiology of medical students from the university of Málaga - Carrasco-Gomez, D.; Chao-Écija, A.; López-González, M. V.; Dawid-Milner, M. S. (Frontiers in Physiology, 2023)
Escape room's popularity has raised over the past years among young adults. It creates a distended competitive environment, where participants collaborate to achieve a common objective through teamwork. We decided to apply this format as a teaching method for medical students at the University of Malaga, Spain. A peer-to-peer physiological cardiorespiratory escape room was designed by intern undergraduate students, collaborating within the Department of Human Physiology. This activity integrated the contents of the Human Physiology syllabus, which were organized into four stages that culminated in a final medical case. Intern students oversaw the design, promotion, preparation and execution of the activity, and were in charge of conducting the evaluation and follow up. The escape room was done in mid-December, after all theoretical and practical contents had been delivered, for four consecutive years, improving from each year's experience. The target group for this activity were second year medical students, who were asked to team up freely in groups of 4-6 students before the start of the activity. The students in each group cooperated with each other while trying to solve the different puzzles and questions in each stage of the escape room. After the activity, the results of the final evaluation exam of these participants were compared against non-participants, who served as a control group. Qualitative feedback was also received from the participants via a special survey that was designed for this task. Results between 2020 and 2023 (three last activities) show that the final mark of the participants was significantly higher than in non-participants (6.39 ± 0.14 vs 5.04 ± 0.2; p<0.0007). The global exam mark also increased in the participants (5.43 ± 0.10 vs 4.44 ± 0.15; p<0.0007). A significant difference was observed in the performance in cardiovascular (p<0.0007) and respiratory-related questions (p<0.0007), which was substantial in the participants. The qualitative feedback received from the participants was mainly positive, indicating an overall acceptance of the format by the students. We conclude that escape room format with a peer-to-peer structure is an efficient teaching tool for medical students performed by medical students in the field of Human Physiology.